Dampak Penerapan Whistleblowing System terhadap InternalFraud Pada PT. Bank Central Asia Periode 2014 – 2017 - Sri Yunawati (Fakultas Ekonomi Universitas Pasir Pengaraian, 2019)
Whistleblowing system is communication internal company to report what / behavior / events relating to the act of fraud , offense against the law , the company , the code of conduct , and a conflict of interest held by investors in internal company. For increase the effectiveness of control system and good corporate governance with on disclosure of complaints ( reporting ), must beformulated policy whistleblowing system are clearly, easily understandable, and could be implemented effectively so inteas to give encouragement and awareness to employees and officials BCA to report the act of his, offense against the law, regulation company, code of conduct, and a conflict of interest occurring in BCA. Internal fraud is divergence/ fraud be done by staff , permanent staff , non permanent employees and / or labor over the outsourcing related to the process of working and operating the bank .With a nominal value of expressed is worth more than Rp 100.000.000,00 (one hundred million rupiah). The result of research is has been done the implementation of whistleblowing system on BCA still have not been able to reduce the level of internal fraud occurs , is based on the number of complaints in the system in 2017 is 17 ( seventeen ) complaints and there are ten cases of misuse of 10 (ten ) conducted by permanent staff .